Legitimation, transmission, and continuity: exploring the heart-of-mind esoteric Buddhist tradition in contemporary China - Xu, Daohua; Liu, Yaoping (Frontiers in Sociology, 2025)
Existing research on legitimation has largely centered on historical and political narratives, overlooking the complex mechanisms through which contemporary practitioners construct, negotiate, and assert religious authority and authenticity. This study examines the processes of legitimation, transmission, and continuity within the Esoteric Buddhist Tradition in contemporary China. Drawing on 18 months of ethnographic fieldwork—including participant observation at three key sites (Yuanyin Temple, the ancient Yuanyin training site, and the Damodong Temple complex)—and 25 semi-structured interviews with monks, ritual specialists, and lay disciples, this research reveals that legitimacy is co-constructed through both internal and external forces. Internally, 84% of informants emphasized charismatic leadership and ritual efficacy as central to sustaining spiritual authority, while 72% highlighted the significance of lineage authenticity. Externally, institutional recognition from provincial Buddhist associations and participation in at least seven inter-sectarian forums between 2022 and 2024 provided crucial validation and public visibility. Furthermore, sustainability practices emerged as adaptive responses to contemporary challenges: 68% of sites integrated environmental ethics into temple management, 56% adopted digital media platforms for ritual dissemination, and 41% developed youth-oriented engagement programs. Collectively, these findings demonstrate that the legitimation, transmission, and continuity of the Esoteric Buddhist Tradition in modern China are dynamically constituted through the interplay between internal charisma, ritual authority, and institutional embeddedness within a rapidly modernizing socio-religious landscape.